2021
DOI: 10.1093/jnci/djab147
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Prostate Cancer Risks for MaleBRCA1andBRCA2Pathogenic Variant Carriers Using Polygenic Risk Scores

Abstract: Background Recent population-based female breast cancer and prostate cancer polygenic risk scores (PRS) have been developed. We assessed the associations of these PRS with breast and prostate cancer risks for male BRCA1 and BRCA2 pathogenic variant carriers. Methods 483 BRCA1 and 1,318 BRCA2 European ancestry male carriers were available from the Consortium of Investigators of Modifiers of BRCA1/2 (CIMBA). A 147-single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…30 Another recent work showed that there is a wide-range of absolute risks for breast cancer and prostate cancer in PV heterozygotes in terms of different genes and across PRS stratification. 31 Our results showed that the PRS acts as a risk modifier for breast cancer and prostate cancer among both the general population and PV heterozygotes in all the well-known cancer susceptibility risk genes. PRS can define a significant proportion of the general population that is at a risk comparable with PV heterozygotes for moderate-risk genes or even more when considering family history.…”
Section: Discussionmentioning
confidence: 56%
“…30 Another recent work showed that there is a wide-range of absolute risks for breast cancer and prostate cancer in PV heterozygotes in terms of different genes and across PRS stratification. 31 Our results showed that the PRS acts as a risk modifier for breast cancer and prostate cancer among both the general population and PV heterozygotes in all the well-known cancer susceptibility risk genes. PRS can define a significant proportion of the general population that is at a risk comparable with PV heterozygotes for moderate-risk genes or even more when considering family history.…”
Section: Discussionmentioning
confidence: 56%
“…A recent study by Barnes et al 47 used a population‐based polygenic risk score‐based approach to determine risk and found that polygenic risk score for prostate cancer based on a population was associated with higher rates of prostate cancer for BRCA1 carriers and BRCA2 carriers. For BRCA2 carriers by age 85, the 5th and 95th percentile prostate cancer risks were reported as 34.1%– 87.6%, respectively 47 …”
Section: Polygenic Risk Scoresmentioning
confidence: 99%
“…PRS for breast, colorectal and prostate cancers in particular may be informative for population-based screening and prevention. 210,[212][213][214][215][216][217][218][219][220] Polygenic background can modify risks for monogenic cancers, and PRS may therefore have utility for refining cancer risk estimates for patients with monogenic cancer variants. 221 For example, the BOADICEA model for breast cancer risk prediction incorporates PRS along with monogenic variants and other risk factors (eg, age, mammographic density) to generate personalized breast cancer risk estimates.…”
Section: Gene-disease Relationships Penetrance and Inclusion On Hered...mentioning
confidence: 99%
“…Polygenic risk scores (PRS) are an emerging tool for cancer risk prediction. The combined effect of many genetic risk variants can be used to construct PRS 212 . PRS may identify a greater proportion of the population at increased risk for cancer than would be identified by traditional genetic testing approaches.…”
Section: Gene‐disease Relationships Penetrance and Inclusion On Hered...mentioning
confidence: 99%
See 1 more Smart Citation